Synovial sarcoma of kidney in a child: A rare presentation - Venkatraman Radhakrishnan; Manikandan Dhanushkodi; Kathiresan Narayanswamy; Anand Raja; Shirley Sundersingh; Tenali Sagar (Wolters Kluwer Medknow Publications, 2016)
There are no reported cases in the literature of primary renal synovial sarcoma in pediatric patients. The management of renal synovial sarcoma has been extrapolated from the management of soft tissue sarcomas at other sites. We present a 4-year-old female who was suspected to have Wilms' tumor. The patient underwent guided biopsy as she did not respond to neoadjuvant chemotherapy for Wilms' tumor. The biopsy was consistent with primary renal synovial sarcoma. The child was treated with change in her neoadjuvant chemotherapy regimen and surgery. The diagnosis of synovial sarcoma was confirmed by demonstrating the t (X, 18) translocation using polymerase chain reaction.